Perlindungan Hukum Bagi Perempuan Sebagai Korban Tindak Pidana Perdagangan Orang Oleh Suami - Mohammad Haris Yusuf Albar; Bambang Pujiono; Fitri Windradi (LPPM Universitas Ekasakti Padang, 2023)
Crimes of human trafficking still often occur to this day, even people who are supposed to be protectors of their wives are willing to sell their wives to other people with the aim of meeting their household needs. This makes it difficult for the government to provide protection to wives who are victims of human trafficking carried out by their husbands, because there could be wives who are unwilling to report their beloved husbands to law enforcement officials for what their husbands have done. In this research, normative legal research is used with a statutory approach, case approach, and conceptual approach. There are various efforts that can be made to provide legal protection to victims of human trafficking carried out by their beloved husband, including preventive and repressive efforts.